Nontypeable Haemophilus influenzae biofilms: role in chronic airway infections - Swords, W E. (Frontiers in Cellular and Infection Microbiology, 2012)
Like many pathogens inhabiting mucosal surfaces, nontypeable Haemophilus influenzae (NTHi) forms multicellular biofilm communities both in vitro and in various infection models. In the past 15 years much has been learned about determinants of biofilm formation by this organism and potential roles in bacterial virulence, especially in the context of chronic and recurrent infections. However, this concept has not been without some degree of controversy, and in the past some have expressed doubts about the relevance of NTHi biofilms to disease. In this review, I will summarize the present information on the composition and potential role(s) of NTHi biofilms in different clinical contexts, as well as highlight potential areas for future work.